Knowledge and awareness of water quality protection issues within local authorities - Gianluca Grilli; John A. Curtis (The Economic and Social Research Institute (ESRI), 2021)
The EU Water Framework Directive (WFD) outlines an integrated framework for water management. The major objective of the WFD is that member states should achieve at least good ecological status of all national waters. This ambitious target can only be achieved with efficient water management governance because water quality is complex and sources of pollution are manifold. Within countries, multiple institutions are responsible for water management, often operating within a hierarchical structure, in which each level has different responsibilities. The top levels of the hierarchy outline the strategy for water management at national level, however most actions with direct impact on water quality occur at the lower levels of the hierarchy. Therefore, it is essential that knowledge and awareness of water management is effectively transferred through the hierarchical structure to the staff responsible for day-to-day activities. In Ireland, daily operations of water quality management are undertaken by the employees of the Local Authorities (i.e. local government), amongst others. This study investigates the level of knowledge and awareness of water quality issues among Local Authority staff within Ireland and the extent to which water protection measures are implemented within core functions of local government. Staff are knowledgeable about high level issues and policy, including institutions responsible for water management, awareness of WFD and river basin management plans. Knowledge and awareness levels are considerably lower on more specific details, including on water quality status and protection measures being implemented within their jurisdictional areas. Overall, the study suggests that there is considerable scope for improvement in knowledge and awareness, and therefore priority towards, water quality and protection issues among Local Authority staff.
Keywords: 330; Gewässerschutz; Wasserversorgung; Wasserpolitik; Kommunalverwaltung; Kommunale Versorgungswirtschaft; Wissensmanagement; Irland